Intact vitreous humor as a potential extracellular matrix hydrogel for cartilage tissue engineering applications. (February 2019) - Lindberg, G.C.J.; Longoni, A.; Lim, K.S.; Rosenberg, A.J.; Hooper, G.J.; Gawlitta, D.; Woodfield, T.B.F.
Graphical abstract: Abstract: Decellularisation of tissues, utilising their biochemical cues, poses exciting tissue engineering (TE) opportunities. However, removing DNA from cartilage (dCart) requires harsh treatments due to its dense structure, causing loss of bioactivity and limiting its application as a cartilaginous extra cellular matrix (ECM). In this study, we demonstrate for the first time the successful application of vitreous humor (VH), a highly hydrated tissue closely resembling the glycosaminoglycan (GAG) and collagen composition of cartilage, as an ECM hydrogel to support chondrogenic differentiation. Equine VH was extracted followed by biochemical quantifications, histological examinations, cytotoxicity (human mesenchymal stromal cells, hMSCs and human articular chondrocytes, hACs) and U937 cell proliferation studies. VH was further seeded with hACs or hMSCs and cultured for 3-weeks to study chondrogenesis compared to scaffold-free micro-tissue pellet cultures and collagen-I hydrogels. Viability, metabolic activity, GAG and DNA content, chondrogenic gene expression (aggrecan, collagen I/II mRNA) and mechanical properties were quantified and matrix deposition was visualised using immunohistochemistry (Safranin-O, collagen I/II). VH was successfully extracted, exhibiting negligible amounts of DNA (0.4 ± 0.4 µg/mg dry-weight) and notable preservation of ECM components. VH displayed neither cytotoxic responses nor proliferation of macrophage-like U937 cells, instead enhancing both hMSC and hAC proliferation. Interestingly, encapsulated cells self-assembled the VH-hydrogel into spheroids, resulting in uniform distribution of both GAGs and collagen type II with increased compressive mechanical properties, rendering VH a permissive native ECM source to fabricate cartilaginous hydrogels for potential TE applications. Statement of Significance: Fabricating bioactive and cell-instructive cartilage extracellular matrix (ECM) derived biomaterials and hydrogels has over recent years proven to be a challenging task, often limited by poor retention of inherent environmental cues post decellularisation due to the dense and avascular nature of native cartilage. In this study, we present an alternative route to fabricate highly permissive and bioactive ECM hydrogels from vitreous humor (VH) tissue. This paper specifically reports the discovery of optimal VH extraction protocols and cell seeding strategy enabling fabrication of cartilaginous matrix components into a hydrogel support material for promoting chondrogenic differentiation. The work showcases a naturally intact and unmodified hydrogel design that improves cellular responses and may help guide the development of cell instructive and stimuli responsive hybrid biomaterials in a number of TERM applications.